A Critique of Females’ Representation in Àyìnlá Ọmọwúrà’s Songs - Adeleye, Adeyemo Olatunde (NIU Journal of Social Sciences, 2024)
Our societies comprise of both male and female with individual playing their expected roles towards the successful growth of the society. Also, in our society, little respect or recognition is given to women based on the culture of the land. Some artists are also conversant in presenting the female as a second fiddle in the society. Therefore, it is on this note that this paper seeks to focus on the critique of females’ representation in Àyìnlá Ọmọwúrà’s song. The research methods involved appropriate and objective analysis of Àyìnlá Ọmọwúrà selected songs from the feminist perspective or point of few. This will assist to determine the effect of the selected songs on the females’ and its implication. At the end, this paper clearly shows and establish the fact that artist sincerely play on the intelligent of the females not minding whose ox is gored. Only the females are point or focus of attack in his song and failed to address the lapses of men who are the real causes of most of female’s accusation. Keywords: Songs, Critique, female, representation.